AN ANALYSIS OF ENGLISH STUDENTS’ ANXIETY IN TOEFL PREDICTION LISTENING COMPREHENSION TEST - Inten Anggelina; Yupika Maryansyah; Ivan Achmad Nurcholis (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the types and the most type of anxiety experienced by English students during the Listening Comprehension section of the TOEFL Prediction Test. Conducted at Muhammadiyah University of Bengkulu, the study surveyed 41 students using a questionnaire to measure different types of anxiety: physical, cognitive, behavioral, emotional, and facilitative. The findings indicate that cognitive anxiety is the most prevalent, characterized by excessive worry and difficulty concentrating. However, facilitative anxiety also emerged as a dominant factor, suggesting that some students channel their stress into motivation. The study highlights the need for strategies to manage anxiety effectively, including enhanced test preparation and anxiety-reducing techniques. Keywords: TOEFL, listening comprehension, anxiety, test anxiety, facilitative anxiety